Memorable Dates. Minister-reformer of Public Health of Ukraine, scientisi, surgeon. - Фомін, П.; Березницький, Я.; Шепетько, Є. (Medicni Perspektivi, 2017)
Memorable Dates. Minister-reformer of Public Health of Ukraine, scientisi, surgeon.